Plastic Surgery Training Worldwide: Part 1. The United States and Europe. Issue 3 (March 2016) - Kamali, Parisa; van Paridon, Maaike W.; Ibrahim, Ahmed M. S.; Paul, Marek A.; Winters, Henri A.; Martinot-Duquennoy, Veronique; Noah, Ernst Magnus; Pallua, Norbert; Lin, Samuel J.
Abstract : Background: Major differences exist in residency training, and the structure and quality of residency programs differ between different countries and teaching centers. It is of vital importance that a better understanding of the similarities and differences in plastic surgery training be ascertained as a means of initiating constructive discussion and commentary among training programs worldwide. In this study, the authors provide an overview of plastic surgery training in the United States and Europe. Methods: A survey was sent to select surgeons in 10 European countries that were deemed to be regular contributors to the plastic surgery literature. The questions focused on pathway to plastic surgery residency, length of training, required pretraining experience, training scheme, research opportunities, and examinations during and after plastic surgery residency. Results: Plastic surgery residency training programs in the United States differ from the various (selected) countries in Europe and are described in detail. Conclusions: Plastic surgery education is vastly different between the United States and Europe, and even within Europe, training programs remain heterogeneous. Standardization of curricula across the different countries would improve the interaction of different centers and facilitate the exchange of vital information for quality control and future improvements. The unique characteristics of the various training programs potentially provide a basis from which to learn and to gain from one another.